PENGARUH PERCEIVED USEFULNESS DAN TRUST TERHADAP KEPUASAN KONSUMEN PADA E- COMMERCE SHOPEE - Latifah, Nunuk; Widayani, Anna; Normawati, Rani Arifah (BISMA: Jurnal Bisnis dan Manajemen, 2020)
The purpose of this study is to analyze and explain the effect of perceived usefulness and trust on consumer satisfaction of Shopee e-commerce. This research conducted in Indonesia that targeted Shopee consumers. Data were collected from the survey by distributing questionnaires to the research respondents. The sample consisted of 86 people selected by a random sampling technique. Data were analyzed using multiple linear regression. Results showed that perceived usefulness and trust have a positive and significant effect on consumer satisfaction. The results of this study also proved that Shopee users assess that the perceived usefulness of the e-commerce applications could facilitate convenience during the online transaction. Meanwhile, trust, in the form of guaranteed transactions and recommendations and ratings from consumers, is a form of support and services provided by Shopee to build consumer trust in Indonesia. Keywords: customer satisfaction, e- commerce, perceived usefulness, Shopee, trust